2020
DOI: 10.3390/biology9030060
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidants in Atherosclerosis Development and Treatment

Abstract: Atherosclerosis can be regarded as chronic inflammatory disease affecting the arterial wall. Despite the recent progress in studying the pathogenesis of atherosclerosis, some of the pathogenic mechanisms remain to be fully understood. Among these mechanisms is oxidative stress, which is closely linked to foam cells formation and other key events in atherosclerosis development. Two groups of enzymes are involved in the emergence of oxidative stress: Pro-oxidant (including NADPH oxidases, xanthine oxidases, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 102 publications
(115 reference statements)
1
91
0
Order By: Relevance
“…SOD is the first line of antioxidant defense system. Under the low concentration of TCS-DT exposure, the SOD activity of heart tissue increases, strengthening the elimination of active oxygen free radicals, so as to avoid the oxidative damage to organism tissues (Li et al, 2012), but they will trigger oxidative stress in the absence of downstream enzymes sufficient to detoxify the final SOD product (Poznyak et al, 2020). Decreased SOD levels are an important indicator of oxidative stress (Akila and Vennila, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…SOD is the first line of antioxidant defense system. Under the low concentration of TCS-DT exposure, the SOD activity of heart tissue increases, strengthening the elimination of active oxygen free radicals, so as to avoid the oxidative damage to organism tissues (Li et al, 2012), but they will trigger oxidative stress in the absence of downstream enzymes sufficient to detoxify the final SOD product (Poznyak et al, 2020). Decreased SOD levels are an important indicator of oxidative stress (Akila and Vennila, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Based on their origins, small molecule antioxidants can be endogenous (e.g., uric acid, coenzyme Q, bilirubin) or exogenous (e.g., vitamins C and E, flavonoid, carotenes). Major antioxidant systems present in the vascular wall include superoxide dismutase, catalase, glutathione peroxidase, thioredoxin, peroxiredoxin [ 73 ]. The dysregulation of oxidant and antioxidant enzymes, such as an inefficient degradation of ROS, an increased activity of oxidant enzymes or a reduced/aberrant activity of antioxidant enzymes, produces an increase in ROS levels which overcome the buffering capacity of ROS scavengers causing oxidative stress [ 74 ].…”
Section: Oxidative Stress and Endothelial Dysfunction And Cvdmentioning
confidence: 99%
“…Superoxide dismutase (SOD) belongs to a family of enzymes that catalyze the conversion of the O2- to H 2 O 2 [ 3 ]. Three isoforms of SODs have been described: SOD1 is found in the cytoplasm and on the inner mitochondrial membrane; SOD2 is located in the mitochondrial matrix, and SOD3 is extracellular [ 73 ]. In endothelial cells, it has been reported that inhibition of SOD1 increased the steady-state levels of O2- and reduced the phosphorylation of extracellular signal-regulated kinases (ERK) 1/2.…”
Section: Oxidative Stress and Endothelial Dysfunction And Cvdmentioning
confidence: 99%
See 2 more Smart Citations